Relationships between work ethics and green management: a case study of Shiraz public hospitals - Mosallanejad , Reyhaneh; Manzari Tavakoli, Hamdollah; Salajegheh , Sanjar; Fatehi Rad, Navid; Arabpour , Alireza (Social Determinants of Health, 2021)
Introduction: Work ethic and green management are crucial issues in the health sector. This study was conducted to design a model on the relationship between work ethic and green management in public hospitals in Shiraz. Methods: Mixed method (qualitative-quantitative) was used in the present study. The statistical sample in the qualitative section to answer the Delphi questionnaire included professors of medical universities and managers of public hospitals in Shiraz. The statistical sample in this section was obtained to be 15 people by using snowball sampling. The statistical population in the quantitative section included 200 staff of Shiraz public hospitals. They selected by stratified sampling method. Data collection tools included Delphi questionnaire and structural equation questionnaire. The quantitative section analysis was performed by SPSS and AMOS software. Results: Based on the results of the Delphi method, 8 main components and 29 sub-components were identified: among them, 4 main components were related to work ethic and 4 main components were related to green management. The results of structural equations showed that the factor loads of green management components including waste management, green human resources, productivity and energy were 0.41, 0.73, 1.09 and 0.60, respectively. Also, the factor loads of work ethic components including dependence, ambition, considerations and cooperation were 0.65, 0.81, 0.89 and 0.75, respectively. Work ethic also affected green management by 0.40. Conclusion: Work ethic affects green management. Health and human considerations in the workplace and ambition in work, productivity and green human resources were the most important components.